Strategi Pemaknaan dalam Memahami Teks Narasi Berbahasa Arab di SMA Terpadu Darut Tauhid Patemon Kerejengan - Sheila Rohmatika Fitria; Ainur Rofiq Sofa (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to examine the strategy of meaning in Arabic language learning at SMA Terpadu Darut Tauhid with a focus on understanding narrative texts. Through a qualitative-descriptive approach, data were obtained from observations of learning activities, documentation, and in-depth interviews with teachers, students, and language program managers. The results of the study indicate that strategies such as Jigsaw, Index Card Match, and direct methods (al-thariqah al-mubasyarah) are effective in improving students' linguistic understanding and contextual values. The implementation of these strategies is carried out in an integrated manner in a daily language-based program, supported by a conducive religious environment. The use of narrative texts, especially the stories of the prophets and companions, not only enriches the mastery of mufradat and tarkib, but also becomes a means of internalizing the values ​​of akhlakul karimah. The challenge of time constraints is overcome through creative approaches such as role-play and short dialogues. This study recommends the importance of integration between linguistic strategies and spiritual values ​​in Arabic language learning in a religious-based educational environment.